Demolish or reuse? – The balance between operational and embodied emissions in the retrofit of commercial buildings. Issue 1 (1st September 2022) - Abbey, D; Arbabi, H; Gillott, C; Ward, W; Tingley, D D
Abstract: There are two clear options for reducing the emissions of poorly-performing buildings: refurbishment of the space to a higher standard or demolition and replacement with a better performing building. Non-residential buildings are subject to the latter of these options more than dwellings due to higher rates of ownership changes. This study assesses the carbon emissions of each of the above options for a poorly-performing retail building in Sheffield, UK. The embodied carbon and operational performance of each scenario are calculated to identify the most sustainable option over a 50 year lifespan. The scenario with the lowest emissions is found to be a retrofit case study relying upon electricity as its sole fuel source. The new build scenarios emitted significantly more carbon over the building's lifespan despite performing better operationally than the refurbishment scenario. It was also found that, due to the decarbonisation of the national grid, relying on gas boilers instead of electric fuel sources would make carbon emissions approximately 2.5x bigger in the refurbishment model, despite being legal under UK building regulations.